Automorphisms of the endomorphism semigroup of a free commutative g-dimonoid - Zhuchok, Y.V. (Algebra and Discrete Mathematics, 2016)
We determine all isomorphisms between the endomorphism semigroups of free commutative g-dimonoids and prove that all automorphisms of the endomorphism semigroup of a free commutative g-dimonoid are quasi-inner.